2021
DOI: 10.21865/ridep59.2.08
|View full text |Cite
|
Sign up to set email alerts
|

Adaptación y Validación del Cuestionario de Compromiso Escolar en Países Iberoamericanos

Abstract: El objetivo de este estudio es adaptar y validar el Cuestionario de Compromiso Escolar desarrollado en Chile en adolescentes escolarizados de Colombia, Uruguay, España y Perú. Para asegurar la equivalencia cultural y lingüística en cada uno de los países, los ítems fueron en primer lugar revisados por siete expertos en educación y posteriormente por treinta adolescentes con características similares a las de la población objetivo. Los cuestionarios fueron aplicados a 1578 estudiantes en los cuatro países, a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
14

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 16 publications
1
12
0
14
Order By: Relevance
“…From the results obtained, we can conclude that school engagement and contextual factors questionnaires in both face-to-face and distance learning contexts present adequate psychometric properties. Starting with the School engagement Questionnaire, the results of the factorial structure analysis showed that both the 7th and 8th grade version and the 5th and 6th grade version obtained a good fit of the data to the structure of a model of three correlated factors (affective, behavioral, and cognitive), which coincides with the theoretical configuration of the concept in pre-pandemic context [ 13 , 14 , 29 , 30 ]. In addition, reliability analyses of the questionnaire showed an adequate internal consistency of the entire scale and its component dimensions.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…From the results obtained, we can conclude that school engagement and contextual factors questionnaires in both face-to-face and distance learning contexts present adequate psychometric properties. Starting with the School engagement Questionnaire, the results of the factorial structure analysis showed that both the 7th and 8th grade version and the 5th and 6th grade version obtained a good fit of the data to the structure of a model of three correlated factors (affective, behavioral, and cognitive), which coincides with the theoretical configuration of the concept in pre-pandemic context [ 13 , 14 , 29 , 30 ]. In addition, reliability analyses of the questionnaire showed an adequate internal consistency of the entire scale and its component dimensions.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, reliability analyses of the questionnaire showed an adequate internal consistency of the entire scale and its component dimensions. In relation to the Contextual Factors Questionnaire, the results of the factor structure analyses showed that both the 7th and 8th grade version and the 5th and 6th grade version obtained a good fit of the data to the structure of a three-factor model (family, teacher, and peers) as well as in the pre-pandemic context [ 15 , 18 , 29 , 30 , 37 ]. Meanwhile, reliability analyses showed that both the complete scale and its component dimensions show adequate internal consistency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En este sentido, no existe consenso sobre qué instrumento es el más adecuado, pues existen deficiencias en cuanto a la adecuación de las propiedades psicométricas y confusión sobre las variables con las que el constructo se relaciona (Sinatra et al, 2015). De aquí la necesidad de contar con revisiones de instrumentos que evalúen el compromiso académico, para visualizarlos y fomentar estrategias para su desarrollo en estudiantes (Lara et al, 2021;Sinatra et al, 2015). Así como, conocer las características e instrumentos de medida del compromiso escolar y de aquellas variables que lo promueven, con la finalidad de mejorar el aprendizaje y bienestar académico de los alumnos y alumnas (Baena-Extremera & Granero-Gallegos, 2013; Caballero et al, 2015ª;Martos et al, 2018;Medrano et al, 2014).…”
Section: Discusión/conclusionesunclassified
“…Tomando en consideración a autores como Caballero et al (2015) y Martos et al (2018), es fundamental conocer las características de este constructo y sus instrumentos de medida aptos para todas las etapas educativas, con el fin de profundizar en el conocimiento del compromiso académico y en su evaluación. Pues el uso de instrumentos no adaptados o validados conlleva a una reducción de la calidad de la investigación y, por ende, de su conocimiento (Lara et al, 2021;Sinatra et al, 2015).…”
Section: Introductionunclassified